2023
DOI: 10.3390/ijms24065780
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Recurrent Neural Network for Predicting Higher Heating Value of Biomass

Abstract: The higher heating value (HHV) is the main property showing the energy amount of biomass samples. Several linear correlations based on either the proximate or the ultimate analysis have already been proposed for predicting biomass HHV. Since the HHV relationship with the proximate and ultimate analyses is not linear, nonlinear models might be a better alternative. Accordingly, this study employed the Elman recurrent neural network (ENN) to anticipate the HHV of different biomass samples from both the ultimate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The subsequent sections comprehensively evaluate the MLPNN performance utilizing graphical and numerical analyses. In addition, the MLPNN accuracy will be compared with another model recently proposed in the literature 61 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The subsequent sections comprehensively evaluate the MLPNN performance utilizing graphical and numerical analyses. In addition, the MLPNN accuracy will be compared with another model recently proposed in the literature 61 .…”
Section: Resultsmentioning
confidence: 99%
“…The literature recently applied recurrent neural networks (RNN) to predict biomass HHV from all proximate and ultimate compositional analyses 61 . Therefore, it is a good idea to compare the prediction accuracy of this RNN with the proposed MLPNN in the current study.…”
Section: Resultsmentioning
confidence: 99%
“…These results show that the ANN is the best model for predicting the value of the HHV variable. Aghel et al (2023) [6] reported the model accuracy for various developed ANN models as R 2 0.83-0.88 and MAE 0.66-0.85, while Afolabi et al (2022) [5] reported 1.21 for the ANN model and 1.01 for the RF model.…”
Section: Discussionmentioning
confidence: 99%
“…The higher heating value is used in the design of energy systems of different sizes and is considered an extremely important parameter for the processes [5]. Aghel et al (2023) [6] state that the relationship between the variables of biomass proximity analysis is not linear, so nonlinear modeling is a better alternative in finding a solution. In addition to the analysis of the HHV as a measure of fuel quality, proximate analysis can provide a detailed insight into the physicochemical composition of the biomass, which is of crucial importance for further modeling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation